Peningkatan Kemampuan Structure and Written Expressions pada TOEFL ITP di SMAS Tunas Bangsa Bintan - Pramusita, Santa Maya; Situmorang, Komilie; Nugroho, Dwi Yulianto (Perkumpulan Kualitama Edukatika Indonesia, 2023)
Structure and written expressions are among the TOEFL ITP tests containing 40 questions. The relatively short processing time and the number of questions that are not small require students to do this test quickly and thoroughly. There need to be special tips and intensive training for students to conquer the structure and written expressions test. This activity aims to share the strategy for working on the TOEFL structure test, with the target of student activities at SMAS Tunas Bangsa Bintan. This activity was held online via the Zoom application and was divided into two meetings with a duration of 90 minutes for each meeting. The material for this activity was prepared based on the pre-test results, which were carried out a few weeks before the activity. The methods used in conveying the material are lectures, exercises, and questions and answers. The data for this activity were collected through questionnaires and documentation. Overall, this activity took place conducive, and students felt helped by it. In addition, from the results of the post-test, it appears that there was an increase in scores after students participated in this activity.